Performance management and development system in South Africa, a necessary evil: Qualitative study - Ozoemena Joan Ibeziako (PLoS ONE, 2025)
Performance management focused on development enhances individual and organisational performance and enables improved services. Achieving performance management objectives is vital for addressing healthcare worker shortages and ensuring equitable, quality healthcare. A weakened South African district-based primary health care system links to inadequate leadership and governance. This study aimed to explore how doctors in primary health care perceive performance management and development systems. The objectives examined what medical officers understand about it and their experiences. Emerging themes may provide insights into enhancing implementation. This study used a qualitative, interpretive, and phenomenological research design. Stratified purposive sampling based on PMDS completion and employment duration led to four focus group discussions with 17 participants. A thematic analysis was performed. The overarching theme was the Performance Management and Development System as a necessary evil, with benefits and challenges. The subthemes included understanding components, comprehending clinic systems to improve outcomes, nurturing employee-supervisor interactions, fostering performance and learning culture, and facilitating personal and professional growth. Additional subthemes included ambiguity in fairness, lack of management capacity, and need for a bottom-up approach and realistic implementation. Effective implementation of a Performance Management and Development System requires managers and supervisors to drive this process strategically. Those responsible for clinical governance should invest in personal development to understand the process and consider appropriate implementation tools.